2012
DOI: 10.7243/2049-9752-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of early and late intravenous infusion of milrinone in pediatric patients undergoing cardiac surgery

Abstract: Objective: This study was done to compare the effects of early and late use of milrinone in pediatric patients undergoing complex cardiac surgery. Design:The study was a prospective randomized study. Setting: Prince Sultan cardiac center, Saudi Arabia. Methods:A prospective study involved 40 pediatric patients undergoing congenital corrective cardiac surgery, classified randomly into two groups (N=20). Group A: Milrinone infusion was started without loading dose, at 0.5mcg/kg/min at the beginning of CPB and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Similar studies in children undergoing various congenital heart surgeries[ 8 ] and in adults with pulmonary hypertension undergoing coronary artery bypass graft[ 9 ] and and/or valve surgeries on CPB were published with very similar results. However, this study is different from those studies that it is done in Fontan circulation and has shown the benefits of initiating the infusion at the beginning of the CPB.…”
supporting
confidence: 55%
“…Similar studies in children undergoing various congenital heart surgeries[ 8 ] and in adults with pulmonary hypertension undergoing coronary artery bypass graft[ 9 ] and and/or valve surgeries on CPB were published with very similar results. However, this study is different from those studies that it is done in Fontan circulation and has shown the benefits of initiating the infusion at the beginning of the CPB.…”
supporting
confidence: 55%
“…A similar study in pediatric patients undergoing congenital corrective cardiac surgery showed that early milrinone increased the mean arterial blood pressure, central venous oxygen saturation, urine output and associated with decreased serum lactate level. [ 15 ] The good results with early uses of milrinone at the beginning of CPB may be related to the increased level of milrinone in the blood and its effect on the tissue perfusion during and after CPB[ 16 ] and other studies showed the same results. [ 6 7 ]…”
Section: Discussionmentioning
confidence: 97%